Bearings of Perceived Product Quality, Skepticism towards Store Promotion and Price Orientation on Online Purchase Intention: A First-Hand Reconnaissance - Sajjan Choudhuri (International Journal of Supply Chain Management, 2018)
Online shopping, also known as e-tailing, is gaining importance every day. There are more people who are using the internet to make apurchase than ever before. This has resulted in competition between online retailers and physical stores. The literature on the subject brings out that perceived product quality influences online purchase intention. In fact perceived product quality is agauge of consumer purchase conduct once consumers have evaluated the product. However, efforts to promote the products by sellers face skepticism of potential buyers which ultimately affects purchase intention. Consumers have diverse shopping orientations which influence purchase intention and price is one of them. It is true that the buyers expect the prices to be lower when buying online but this is also true that in thecase of customized and conspicuous consumption price plays a limited role. For the customized products buyers are willing to pay extra.The data for this project was collected with the help of a questionnaire. The questions were constructed with the help of published literature and standardized statements were considered. A five point Likert type scale was used to get responses.Reliability and validity tests were run on the constructs for testing the consistency before multiple regression was employed to arrive at results. The results show that perceived product quality, price orientation and skepticism towards online promotion have a significant effect on online Purchase intention